The effectiveness and safety of Chaiqin Qingning Capsule in upper respiratory tract infections with fever: A prospective, double-blinded, randomized, multicenter controlled trial. (September 2022) - Xu, Xiangru; Zhang, Wen; Wu, Xinxin; Sun, Yuting; Yang, Hongqiang; Pu, Yuting; Zhou, Shuang; Fang, Bangjiang
Abstract: Background and aim: Presently, over-the-counter drugs that can treat upper respiratory tract infections (URTI) are rarely effective and safe. Chaiqin Qingning Capsule (CQQNC), a Chinese patent medicine, which has been verified by long-term clinical practice is recommended by Chinese experts for the treatment of URTI with fever. This study conducted a prospective, double-blinded, randomized, multicenter controlled trial to evaluate the effectiveness and safety of CQQNC in the treatment of URTI. Methods: The study was conducted at 4 clinical centers in China. Eligible subjects were recruited and randomized 1:1 to the CQQNC group and Qingkailing Capsule (QKLC) group. Both groups were administered orally three times a day for three consecutive days. Primary outcomes were the antipyretic onset time and the temperature recovery time. Secondary outcomes included the symptom disappearance rate, symptom score, and drug safety assessment. Results: A total of 269 subjects were analyzed (134 subjects in the CQQNC group, 135 subjects in the QKLC group). The antipyretic onset time and the temperature recovery time were significantly shortened in the CQQNC group (median: 5 h vs. 10 h, p  < 0.0001, median: 19 h vs. 27 h, p  < 0.0001). CQQNC was more effective than the QKLC in improving the symptoms of pharyngodynia and rhinobyon (85.07% vs. 71.11%, p  = 0.008; 76.99% vs. 64.41%, p  = 0.043), and in im p roving the overall symptom scores (−15.10 ± 3.23 vs. −13.35 ± 3.58, p  < 0.0001). During the trial, no serious adverse events were reported in the two groups. Conclusion: CQQNC is effective and safe in the treatment of URTI with fever, and worthy of clinical application. (http://www.chictr.org.cn, ChiCTR-IPR-16009049). Highlights: Upper respiratory tract infection (URTI), also known as common cold, is the most frequently experienced disease among humans. The acute URTI can cause physical discomfort and high health care costs but there are no universally accepted therapies. Chaiqin Qingning Capsule had quick antipyretic effects and advantages in relieving symptoms of pharyngodynia and rhinobyon. In conclusion, Chaiqin Qingning Capsule is safe in use and has good therapeutic effects in the treatment of URTI with fever.